Security Vulnerabilities and Countermeasures for Time Synchronization in TSCH Networks - Yang, Wei; Wan, Yadong; He, Jie; Cao, Yuanlong (Wireless Communications and Mobile Computing, 2018)
Time-slotted channel hopping (TSCH), which can enable highly reliable and low-power wireless mesh networks, is the cornerstone of current industrial wireless standards. In a TSCH network, all nodes must maintain high-precision synchronization. If an adversary launches a time-synchronization attack on a TSCH network, the entire network communication system can be paralyzed. Thus, time-synchronization security is a key problem in this network. In this article, time synchronization is divided into single-hop pairwise, clusterwise, and three-level multihop according to the network scope. We deeply analyze their security vulnerabilities due to the TSCH technology itself and its high-precision synchronization requirements and identify the specific attacks; then, we propose corresponding security countermeasures. Finally, we built a test bed using 16 OpenMoteSTM nodes and the OpenWSN software to evaluate the performance of the proposed scheme. The experimental results showed that serious security vulnerabilities exist in time-synchronization protocols, and the proposed countermeasures can successfully defend against the attacks.